2019
DOI: 10.3390/colloids3010032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Printed Multilayer OLED Fabrication through Slot Die Coating, Gravure and Inkjet Printing, and Their Combination

Abstract: In this study, multilayer organic light-emitting diodes (OLEDs) consisting of three solution-processed layers are fabricated using slot die coating, gravure printing, and inkjet printing, techniques that are commonly used in the industry. Different technique combinations are investigated to successively deposit a hole injection layer (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS)), a cross-linkable hole transport layer (N,N′-bis(4-(6-((3-ethyloxetan-3-yl)methoxy)-hexyloxy)phenyl)-N,N′-bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
0
34
0
1
Order By: Relevance
“…In terms of throughput, for instance in the context of OLEDs, typical material deposition speeds by inkjet printing, slot-die coating and gravure printing are in the 0.1-5 m s −1 range 23 . Evidently, the speeds used in this first demonstration of molecular-gate-based patterning (≤3 mm s −1 ) fall short of those for these established techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of throughput, for instance in the context of OLEDs, typical material deposition speeds by inkjet printing, slot-die coating and gravure printing are in the 0.1-5 m s −1 range 23 . Evidently, the speeds used in this first demonstration of molecular-gate-based patterning (≤3 mm s −1 ) fall short of those for these established techniques.…”
Section: Resultsmentioning
confidence: 99%
“…4,6 . These can be broadly classified into light-based methods such as photolithography 16 and laser-induced forward transfer (LIFT) 17,18 ; printing methods such as inkjet, vapour jet and aerosol jet [19][20][21][22][23] , and contact methods such as hard and soft imprint lithography [24][25][26] . Of these, photolithography represents the most mature technology, with a further advantage being its high spatial resolution (~1 μm in large-field proximity-mode implementations).…”
mentioning
confidence: 99%
“…[10][11][12] More studies can be found based on sheet-tosheet printing processes. [13][14][15][16][17][18][19] But only a few studies reported all solution-processed OLEDs compared to OPVs. [20][21][22][23][24][25] The choice of the materials is the first step to address a lowcost R2R fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…The large area coating of organic electronic devices is an active research area due to the potential to deliver next-generation printed electronics at ultra-low costs. Roll-to-roll and pattern coatings are the most common methods used for the fabrication of multi-layer organic electronic devices such as organic-light-emitting-diodes (OLEDs) 1 , photovoltaics 2 , sensors 3 , and transistors 4 . One of the most user-friendly and inexpensive methods is slot-die coating.…”
Section: Introductionmentioning
confidence: 99%